Residential greenness attenuated association of long-term air pollution exposure with elevated blood pressure: Findings from polluted areas in Northern China - Mei, Yayuan; Zhao, Jiaxin; Zhou, Quan; Zhao, Meiduo; Xu, Jing; Li, Yanbing; Li, Kai; Xu, Qun (Frontiers in Public Health, 2022)
Background: Evidence on the hypertensive effects of long-term air pollutants exposure are mixed, and the joint hypertensive effects of air pollutants are also unclear. Sparse evidence exists regarding the modifying role of residential greenness in such effects. Methods: A cross-sectional study was conducted in typically air-polluted areas in northern China. Particulate matter with diameter <1 µm (PM1), particulate matter with diameter <2.5 µm (PM2.5), particulate matter with diameter <10 µm (PM10), nitrogen dioxide (NO2), sulphur dioxide (SO2), and ozone (O3) were predicted by space–time extremely randomized trees model. We used the Normalized Difference Vegetation Index (NDVI) to reflect residential green space. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were examined. We also calculated the pulse pressure (PP) and mean arterial pressure (MAP). Generalized additive model and quantile g-computation were respectively conducted to investigate individual and joint effects of air pollutants on blood pressure. Furthermore, beneficial effect of NDVI and its modification effect were explored. Results: Long-term air pollutants exposure was associated with elevated DBP and MAP. Specifically, we found a 10-μg/m3 increase in PM2.5, PM10, and SO2 were associated with 2.36% (95% CI: 0.97, 3.76), 1.51% (95% CI: 0.70, 2.34), and 3.54% (95% CI: 1.55, 5.56) increase in DBP; a 10-μg/m3 increase in PM2.5, PM10, and SO2 were associated with 1.84% (95% CI: 0.74, 2.96), 1.17% (95% CI: 0.52, 1.83), and 2.43% (95% CI: 0.71, 4.18) increase in MAP. Air pollutants mixture (one quantile increase) was positively associated with increased values of DBP (8.22%, 95% CI: 5.49, 11.02) and MAP (4.15%, 95% CI: 2.05, 6.30), respectively. These identified harmful effect of air pollutants mainly occurred among these lived with low NDVI values. And participants aged ≥50 years were more susceptible to the harmful effect of PM2.5 and PM10 compared to younger adults. Conclusions: Our study indicated the harmful effect of long-term exposure to air pollutants and these effects may be modified by living within higher green space place. These evidence suggest increasing residential greenness and air pollution control may have simultaneous effect on decreasing the risk of hypertension.